Prevention of hypertension in patients with pre-hypertension: Protocol for the PREVER-prevention trial - Fuchs, Flávio D.; Fuchs, Sandra C.; Moreira, Leila B.; Gus, Miguel; Nóbrega, Antônio C.; Poli-de-Figueiredo, Carlos E.; Mion, Décio; Bortoloto, Luiz; Consolim-Colombo, Fernanda; Nobre, Fernando; Coelho, Eduardo B.; Vilela-Martin, José F.; et al. (Springer Nature, 2011)
Background: Blood pressure (BP) within pre-hypertensive levels confers higher cardiovascular risk and is an intermediate stage for full hypertension, which develops in an annual rate of 7 out of 100 individuals with 40 to 50 years of age. Non-drug interventions to prevent hypertension have had low effectiveness. In individuals with previous cardiovascular disease or diabetes, the use of BP-lowering agents reduces the incidence of major cardiovascular events. In the absence of higher baseline risk, the use of BP agents reduces the incidence of hypertension. The PREVER-prevention trial aims to investigate the efficacy, safety and feasibility of a population-based intervention to prevent the incidence of hypertension and the development of target-organ damage.Methods: This is a randomized, double-blind, placebo-controlled clinical trial, with participants aged 30 to 70 years, with pre-hypertension. The trial arms will be chlorthalidone 12.5 mg plus amiloride 2.5 mg or identical placebo. The primary outcomes will be the incidence of hypertension, adverse events and development or worsening of microalbuminuria and of left ventricular hypertrophy in the EKG. The secondary outcomes will be fatal or non-fatal cardiovascular events: myocardial infarction, stroke, heart failure, evidence of new sub-clinical atherosclerosis, and sudden death. The study will last 18 months. The sample size was calculated on the basis of an incidence of hypertension of 14% in the control group, a size effect of 40%, power of 85% and P alpha of 5%, resulting in 625 participants per group. The project was approved by the Ethics committee of each participating institution.Discussion: The early use of blood pressure-lowering drugs, particularly diuretics, which act on the main mechanism of blood pressure rising with age, may prevent cardiovascular events and the incidence of hypertension in individuals with hypertension. If this intervention shows to be effective and safe in a population-based perspective, it could be the basis for an innovative public health program to prevent hypertension in Brazil.Trial Registration: Clinical Trials NCT00970931. © 2011 Fuchs et al; licensee BioMed Central Ltd.
Keywords: amiloride; beta adrenergic receptor blocking agent; chlortalidone; dipeptidyl carboxypeptidase inhibitor; diuretic agent; hydrochlorothiazide; atherosclerosis; blood pressure measurement; cardiovascular risk; clinical protocol; cost effectiveness analysis; diabetes mellitus; double blind procedure; drug efficacy; drug safety; heart infarction; heart left ventricle hypertrophy; hypertension; hypokalemia; insulin resistance; ischemic heart disease; low drug dose; microalbuminuria; obesity; outcome assessment; prehypertension; randomized controlled trial; sodium restriction; sudden death; vascular disease